Isolation, characterization and identification of roundup degrading bacteria from the soil and gut of Macrotermes michaelseni - Budambula, N. L. M.; Ogot, H. A.; Boga, H. I.; Tsanuo, M.; Andika, D.O.; Ogola, H. J (My University, 2013)
Roundup degrading bacteria were isolated from the soil and gut of fungus cultivating termites Macrotermes michaelseni using MM7 media supplemented with the pesticide as the sole source of carbon and energy. The isolates were gram negative rods the isolate from the soil was designated GS1 while that from termite gut was designated GT2. The 16S rRNA gene sequence of the isolates revealed that isolates Both isolates GS1 and GT2 are closely related to Enterobacter sp AY 0822447 with 99% sequence similarity. The results of this study highlight the potential of these bacterial isolates to be used in bioremediation.
Keywords: Roundup; bioremediation; Macrotermes michaelseni; Enterobacter